2023
DOI: 10.29333/iji.2023.16147a
|View full text |Cite
|
Sign up to set email alerts
|

The positive meaning of the use of Interactive Simulation eduMedia in the subject of Light Waves in Secondary School in Morocco

Abstract: This work aims to study the impact of the use of the interactive simulation eduMedia, on the understanding and learning of Moroccan students in the qualifying secondary of the second year of the scientific baccalaureate option physical sciences at the high school Abdellah Laroui of the city of Fez. Using the pre-test and post-test methodology with a simulation group (24 students) and an experiment group (24 students) during the school year 2021-2022, the data were then analyzed using the IBM SPSS 21 statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…In between, we observed high motivation in students after using PhET simulations, thus simulations are effective tools to increase motivation, this claim is supported by several of the researchers [9,[42][43][44][45][46][47][48][49], Furthermore, the results of this research showed that simulations can increase students' engagement in the learning process. These results are consistent with the findings of [28,31,32,43].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In between, we observed high motivation in students after using PhET simulations, thus simulations are effective tools to increase motivation, this claim is supported by several of the researchers [9,[42][43][44][45][46][47][48][49], Furthermore, the results of this research showed that simulations can increase students' engagement in the learning process. These results are consistent with the findings of [28,31,32,43].…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, this study has shown that PhET simulation can integrate students into a learning environment. Thus, we can confirm that the adoption of PhET simulations improves the interactive exchange between learners [40,42].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation